Stitching a new garment: Considering the future of the speech–language therapy profession globally - Bea Staley; Marise Fernandes; Ellen Hickey; Helen Barrett; Karen Wylie; Julie Marshall; Mershen Pillay; Harsha Kathard; Ryann Sowden; David Rochus; Carol E. Westby; T. Rosario Roman; et al. (South African Journal of Communication Disorders, 2022)
Providing equitable support for people experiencing communication disability (CD) globally is a historical and contemporary challenge for the speech–language therapy profession. A group of speech–language therapists (SLTs) with ongoing and sustained experiences in Majority and Minority World contexts participated in five virtual meetings in 2021. The aim of these meetings was to develop provocative statements that might spur a global discussion among individuals and organisations that support people experiencing CD. The following questions were discussed: What is our vision for the future of the profession globally? What are the global challenges around access to speech–language therapy services?